Study on the Retreatment, Outcome, and Potential Predictors of Recurrence in Patients With Recurrence of Hepatitis B After Functional Cure - Lin, Xiao; Song, Aixin; Lu, Junfeng; Zheng, Sujun; Hu, Zhongjie; Ma, Lina; Cao, Zhenhuan; Li, Hong; Zheng, Yanhong; Ren, Shan; Chen, Xinyue (Frontiers in Immunology, 2022)
Background: Studies about the retreatment and predictors for patients with hepatitis B recurrence after functional cure are rare. This study aimed to evaluate the effect of retreatment, outcome, and potential predictors of recurrence in patients with recurrence after functional cure. Methods: A long-term follow-up was conducted with 32 cumulatively obtained patients who relapsed after cessation of pegylated interferon (Peg-IFN) based antiviral treatment. The decision of whether to retreatment or which therapeutic method to use [Peg-IFN or nucleos(t)ide analogue (NAs)] was based on the patient’s preferences and wishes. The rate of achieving functional cure, and the clinical outcomes of different therapeutic methods were analyzed. Hepatitis B surface antibody (anti-HBs) and hepatitis B core antibody (anti-HBc) levels were detected in patients with blood samples during follow-up to evaluate the predictive ability of recurrence. Results: The follow-up time of 32 recurrence cases was 42 - 532 weeks after recurrence (median 226 weeks). In the 20 patients who received retreatment (15 received Peg-IFN and 5 received NAs only), the rate of functional cure was 65.0% (13/20) and 86.7% (13/15) in the patients retreated with Peg-IFN. Three cases experienced recurrence again. 5 patients received NAs treatment, and no functional cure was achieved. No drug intervention was administered for 12 patients, 2 of them with HBV DNA spontaneous clearance, and one patient achieved spontaneous HBsAg clearance during follow-up. Patients who relapsed after functional cure with Peg-IFN treatment did not have liver cirrhosis or hepatocellular carcinoma during the follow-up, regardless of whether they received retreatment. Anti-HBs and anti-HBc levels at the end of therapy were predictors of recurrence (p<0.001, p=0.023). The value of combining the above two indicators in predicting recurrence was further improved, the areas under the receiver operating characteristic curves were 0.833, at combining predictors > -0.386, the predictive sensitivity and specificity for recurrence were 86.67% and 90.62%. Conclusion: The functional cure rate was above 80% for patients with recurrence treated by Peg-IFN. During the follow-up, liver cirrhosis and hepatocellular carcinoma were not observed in all recurrence cases. High levels of anti-HBs and anti-HBc at the time of drug discontinuation are less likely to relapse.